Optimization of recombinant E. coli protein expression in growth medium - Duvnjak, Petar (My University, 2007)
With the onset of novel genomic sequence data, much effort is now being taken to discover the role of many genes and the corresponding proteins that remain unknown. One of the limiting steps in such efforts has been the production of recombinant proteins in E. coli using bacterial expression systems. In this current work, several studies were initiated to address the issues affecting recombinant protein expression. These studies specifically focus on the aspects of protein expression and solubility levels, bacterial growth medium design, and expression vector design. While earlier attempts were aimed at comparing commercial expression systems (T5 and T7 RNA polymerase-based systems), later work on vector design showed that vectors with lower lac repressor dosing were optimal for the expression of higher levels of protein in E. coli. Similar collaborative work focused on a factorial-designed growth medium experiment. Results showed optimal growth medium conditions for the expression of two model proteins, Photinus luciferase and enhanced green fluorescent protein (eGFP). Our current work is being directed at the comparison of expression levels and solubility for proteins expressed in vectors containing the Trigger Factor versus maltose binding protein fusion proteins.
46 p.
Keywords: Biochemistry